Papillitis: A rare complication of severe sepsis - (:unkn) unknown (My University, 2008)
A 12-year-old girl was admitted to the emergency room as a result of a vehicle accident with a large tissue defect in the gluteal and perineal region. She was diagnosed as having sepsis and on the 23rd day of her intensive care unit stay she complained of a sudden loss of vision. On physical examination, her pupils were mid-dilated and pupillary reflexes were bilaterally sluggish. The Marcus Gunn sign was negative. Fundoscopic examination revealed bilateral papilledema with peripapillary and periretinal hemorrhage. Cranial diffusion and angiographic magnetic resonance imaging (MRI) studies showed no pathology. MRI examination of the optic nerve was normal. Papillitis was prediagnosed. Although patients in severe sepsis are prone to develop papillitis, the diagnosis of papillitis in these patients is very rare. As many of these patients are sedated, or have an altered mental status, they are not able to express the symptoms of papillitis. In critical care practice, periodic fundoscopic examination should be considered for the early diagnosis and the detection of papillitis in septic patients.
Keywords: Intensive care unit; Loss of vision; Papillitis; Sepsis